IMPLEMENTASI RUMAH TAMAN BACA DALAM MENINGKATKAN BUDAYA LITERASI DI DESA CILANGKARA - Nuraini, Ade Indah; Ash Shabah, Musyaffa Amin; Rahmawati, Rafika (An-Nizam, 2024)
Reading parks are places to collect various reading materials and care for literacy, especially for the surrounding community. Literacy culture needs to be improved along with the times and technological advances. The implementation of this program is to build reading parks starting from early childhood to elementary school children and all students who need to be encouraged from an early age about the culture of literacy so that they are not complacent and addicted to technology. Reading is the main capital for the progress of all students, therefore reading hobbies need to be grown in society from an early age. Indonesia is a country with a very low literacy culture, to the point that UNESCO states that Indonesia is in the second lowest position in the world. This is very concerning. Therefore, this community service in KKN increases interest in reading by starting from the smallest scope, namely by establishing a Reading Park in Cilangkara Village, Serang Baru District. The purpose of this service is to increase interest in reading among children and adolescents in Cilangkara Village. The community service method applies community education. The results of the service have a significant impact in the form of easier access to various reading materials, thus encouraging interest in reading among the community.